Relationship between nutritional status and bronchopneumonia incidence in toddlers at Cut Meutia Hospital North Aceh - Kenedi, Tasya Eka Putri; Khairunnisa, Cut; Fardian, Nur (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Bronchopneumonia is an inflammation of the lung parenchyma that extends to the bronchioles. This condition occurs due to infection that spreads directly through the respiratory tract or bloodstream, causing the accumulation of inflammatory exudate in and around the alveoli that interferes with normal gas exchange and has the potential to trigger serious respiratory disorders. In Indonesia, in 2022, bronchopneumonia was recorded as the leading cause of death for toddlers aged 12-59 months. Risk factors such as nutritional status are known to play an important role in the increasing incidence and mortality due to bronchopneumonia. This study aims to analyze the relationship between nutritional status and the incidence of bronchopneumonia in toddlers at the Cut Meutia Hospital, North Aceh in 2023-2024. This study is an observational analytical study with a cross-sectional design. Data were obtained from medical records of 65 toddlers with bronchopneumonia collected using the total sampling technique. The results of this study showed that the majority of sufferers were female, with a median age of toddlers with bronchopneumonia being 16 months. The median weight of toddlers was 8,6 kg and the average height reached 73,37 cm. Most toddlers affected by bronchopneumonia had good nutritional status and mild disease severity. Statistical analysis using the Chi-Square test showed a p value <0,05, indicating a significant relationship between nutritional status and the incidence of bronchopneumonia in toddlers at the Cut Meutia Hospital, North Aceh in 2023-2024. The results of this study indicate that monitoring nutritional status in toddlers is very important to reduce the severity of bronchopneumonia. Therefore, health intervention programs, such as nutritional education for parents and the provision of balanced nutritious food, need to be intensified to reduce the severity of bronchopneumonia.